Implementación del procedimiento para el control del producto no conforme en una planta torrefactora de café (2009)
Implementation of the procedure for controlling nonconforming product during the processing of green coffee to roasted coffee beans in the roasters factory, describing the methodology followed to identify, monitor and provide treatment to non-conforming products with the characterizations requirements according to the Quality Management System